A New Approach for Conversion of Eucalyptus Lignocellulosic Biomass into Cellulose Nanostructures: A Method that Can Be Applied in Industry - Souza, Alana G. de; De Lima, Giovanni F.; Rodrigues, Rita C. L. B.; Cesarino, Ivana [UNESP]; Leão, Alcides L. [UNESP]; Rosa, Derval S. (Taylor & Francis, 2019)
This study aimed to explore the use of eucalyptus sawdust for the extraction of nanocellulose. This residue was purified with a three-steps pretreatment and ball milled for the isolation of nanocellulose. The method proposed can be industrially applied due to the use of reactor and ball mill and can be used for a variety of cellulose sources. Cellulose was the main component detected in the eucalyptus residues, as observed after the characterizations. The nanostructures showed an average size of 192 nm and high crystallinity and thermal stability. The current study demonstrated that the nanocellulose could be obtained to commercial-scale applications.
Keywords: Bio-residue; cellulose nanostructures; chemical composition; crystallinity; morphology